Half-squat or jump squat training under optimum power load conditions to counteract power and speed decrements in Brazilian elite soccer players during the preseason - Loturco, I.; Pereira, L. A.; Kobal, R.; Zanetti, V.; Gil, S.; Kitamura, K.; Cavinato Cal Abad, C.; Nakamura, F. Y. (Journal of Sports Sciences, 2015)
The purpose of this study was to test which specific type of exercise (i.e., jump squat (JS) or half-squat (HS)) is more effective at maintaining speed and power abilities throughout a preseason in soccer players. Twenty-three male soccer players were randomly allocated into two groups: JS and HS. The mean propulsive power, vertical jumping ability, and sprinting performance were evaluated before and after 4 weeks of a preseason period. The optimum power loads for the JS and HS exercises were assessed and were used as load-references. The soccer players performed 10 power oriented training sessions in total. Both JS and HS maintained power in JS and speed abilities (P > 0.05, for main effects and interaction effect) as indicated by ANCOVA. Both groups demonstrated reduced power during HS (ES = -0.76 vs. -0.78, for JS and HS, respectively); both groups improved acceleration (ACC) from 5 to 10 m (ES = 0.52). JS was more effective at reducing the ACC decrements over 0-5 m (ES = -0.38 vs. -0.58, for JS and HS, respectively). The HS group increased squat jump height (ES = 0.76 vs. 0.11, for HS and JS, respectively). In summary, JS is more effective in reducing the ACC capacity over very short sprints while HS is more effective in improving squat jump performance. Both strategies improve ACC over longer distances. New training strategies should be implemented/developed to avoid concurrent training effects between power and endurance adaptations during professional soccer preseasons.